Available status and changing trend of micronutrients in floodplain soils of Bangladesh (SAARC Journal of Agriculture, 2018)
Soil micronutrient deficiency has arisen in Bangladesh as a consequence of soil fertility depletion with time. Increasing cropping intensity and cultivation of modern varieties with high yield potential are the major reasons of nutrient depletion from soil, which results in decline of crop yield. With an objective of studying delineation of soil micronutrient status, their depleting trend over time, relationship with other soil variables and interrelationship among micronutrients, a study was carried out in Old Meghna Estuarine Floodplain (AEZ 19) soils of the country. In the present study, soil analysis of top soils (0-15 cm soil depth) shows that availability of Zn and B declined after a decade of time. However for other micronutrients, viz. Cu, Mn and Fe, still prevailing high status. Micronutrient levels of subsoil (15-30 cm soil depth) were in general lower than those of top soils. The soil Zn had significant positive correlation with clay content (r=0.712**) and its availability was found influenced more by clay fraction in case of higher Zn concentration (>1.35 μg g-1) than lower concentration (